2020
DOI: 10.9734/arrb/2020/v35i1230323
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS Analysis and Antimalarial Activity of Methanolic Leaf Extract of Carica papaya against Plasmodium berghei NK65 Infection in Swiss Mice

Abstract: Aim: The study determines the GC-MS and the anti-malarial activity of methanolic leaf extract of Carica papaya in Swiss mice infected with Plasmodium berghei NK65. Study Design: The experimental study lasted for five weeks. Place of Study: Department of Chemical Sciences (Biochemistry Unit) and animal House unit in Department of Biological Sciences (Environmental Biology Unit), School of Pure and Applied Sciences, Lagos State Polytechnic, Ikorodu, Lagos, Nigeria. Study Design and Methodology:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…This is a clear positive indication that that the antibacterial activities of aqueous red onion against Staphylococcus aureus and Escherichia coli may be due to the presence of Z, Z-9,12-Octadecadienoic acid and n-Hexadecanoic acid since they constitute 60.56% of the constituent of the extract of red onion. Momoh et al [5] study shows that 9, 12-octadecadienoic acid (Z,Z)possess hepatoprotective, hypocholesterolemic, antiarthritic, anti-inflammatory, anti-histaminic and nematicidal activities. n-Hexadecanoic acid (C 16 H 32 O 2 ) is the second most abundant compound found in the red onion with peak area of 10.06% and retention time of 14.874.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a clear positive indication that that the antibacterial activities of aqueous red onion against Staphylococcus aureus and Escherichia coli may be due to the presence of Z, Z-9,12-Octadecadienoic acid and n-Hexadecanoic acid since they constitute 60.56% of the constituent of the extract of red onion. Momoh et al [5] study shows that 9, 12-octadecadienoic acid (Z,Z)possess hepatoprotective, hypocholesterolemic, antiarthritic, anti-inflammatory, anti-histaminic and nematicidal activities. n-Hexadecanoic acid (C 16 H 32 O 2 ) is the second most abundant compound found in the red onion with peak area of 10.06% and retention time of 14.874.…”
Section: Discussionmentioning
confidence: 99%
“…The compound has antibacterial and antifungal activities [21]. Momoh et al [5] study shows that n-Hexadecanoic acid has antibacterial, antifungal, and anti-inflammatory activities. Powered red onion extracted with six different organic solvents (methanol, acetone, chloroform, benzene, petroleum ether and ethyl acetate) were analyze for their chemical constituent using GC-MS. A total of 43 compounds were identified by GC-MS analysis and out of them dodecanoic acid was found common in all the extracts [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garba and Garba [41] study shows that Cis-9-Octadecenoic acid isolated from Landolphia Owariensis plant possess anti-diarrhoeal properties. Different study have reported that n-Hexadecanoic acid possess anti-inflammatory, antibacterial and antifungal activities [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite profiles have been obtained from various medicinal plants, including: Curucuma species [9], Carica papaya leaf [10], Hunteria umbellata seed extract [11], hexane leaf, stem and root extracts of Azadirachta indica A. Juss [12], methanolic root, stem and leaf extracts of Vernonia amygdalina [13], Carica papaya seed oil [14], Rehmannia glutinosa using GC-MS combined with multivariate statistical analysis [15] and Azadirachta indica root [16].…”
Section: Introductionmentioning
confidence: 99%